Media Sosial Instagram Sebagai Komunikasi Dakwah Terhadap Peningkatan Pengetahuan Agama Pada Gen Z - Arista, Fiansi Dwi; Elsa; Razzaq, Abdur; Nugraha, Muhamad Yudistira (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
Social media, especially Instagram, has become an effective tool in spreading da’wah among Generation Z (Gen Z). This generation has a tendency to access information quickly, visually, and interactively, so Instagram is the right media to convey Islamic teachings. This research uses a qualitative method with a literature review approach to analyze how Instagram plays a role in the transformation of da’wah, the communication strategies applied, and its effect on increasing religious knowledge in Gen Z. The results showed that Instagram is able to make da’wah more interesting and easy to understand through features such as image uploads, short videos, and live broadcasts. However, there are challenges in information validity and algorithm effects that can limit users’ perspectives. Therefore, good digital literacy is needed so that this media can be optimally utilized in increasing religious understanding among Gen Z.